Model Pembelajaran Kooperatif Tipe Pair Check untuk Membangun Keterampilan Bertanya Produktif Siswa - Dwi Ermavianti; Wahyu Sulistyorini (Faculty of Engineering, Universitas Negeri Yogyakarta, 2016)
This study aimed for (1) developing the students’ productive questioning ability in the subject of Anatomy and Physiology and (2) improving the students’ productive cognitive learning. This classroom action study was conducted for the X grade students of the Department of Make up and Beauty Teraphy II. It was undertaken during the odd semester of the academic year of 2014/2015. The data was collected by participatory monitoring, questionnaires, and documentary study. The data resulted from the observation, the interviews, and the discussions with collaborators were analysed, identified, interpreted, validated, and inferred descriptively. The results revealed the students’ productive questioning ability development in the subject of Anatomy consists of 9 stages: the concept explanation, groups division, texts distribution, pair-check assignments, role shifts, answers validation, counseling and directing, correct answers validation, and rewards distribution. In the preliminary condition, the students’ questioning ability was scored and categorised as fair. In the second cycle, it achieved higher score and was categorised as good. It was proved by the higher frequency of questions and the more productive reading ability of the students. The students’ performance in the first cycle that was categorised as good and very good were 61.3% and 9.67% respectively. While in the second cycle, 12 students with the percentage of 38.70% were categorised as good and 15 students with the percentage of 48.30% were categorised as very good in productive questioning.Penelitian ini bertujuan untuk (1) membangun keterampilan bertanya produktif siswa pada mata pelajaran anatomi dan fisiologi dan (2) mengembangkan cara berpikir siswa agar terampil secara produktif. Penelitian ini menggunakan disain Penelitian Tindakan Kelas, dengan setting kegiatan pembelajaran dilaksanakan pada semester ganjil bagi siswa kelas X Tata Kecantikan 2 tahun ajaran 2014/2015. Teknik pengumpulan data menggunakan pemantauan partisipatif, kuisioner, dan studi dokumentasi. Data hasil pengamatan, wawancara, diskusi dengan kolaborator dan dokumen dianalisis secara deskriptif, identifikasi, interprestasi, validasi dan inferensi. Hasil dari penelitian adalah membangun keterampilan bertanya produktif siswa pada mata pelajaran anatomi terdapat 9 tahapan antara lain: menjelaskan konsep, membagi siswa dalam kelompok, membagikan teks, melaksanakan pair check, siswa bertukar peran, mencocokkan jawaban, membimbing dan mengarahkan, mengecek jawaban benar, dan mendapatkan reward. Kondisi awal yang menunjukkan siswa ketika mengungkapkan pertanyaan secara singkat dan jelas memperoleh kriteria cukup. Pada akhir kegiatan (siklus 2) mengalami peningkatan memperoleh kriteria baik. Hal ini terlihat dari frekwensi siswa dalam bertanya mengalami peningkatan, dan mampu membaca secara produktif sesuai dengan teks/bacaan yang diberikan oleh guru. Indikator kinerja di siklus 1 memperoleh kriteria baik (61,3%) dan kriteria sangat baik (9,67%). Pada siklus 2 sebanyak 12 orang (38,70%) siswa memperoleh predikat baik, dan sebanyak 15 orang (48,30%) memperoleh predikat sangat baik dalam bertanya produktif.